1986
DOI: 10.1159/000199295
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Effect of Truncal Vagotomy on the Rat Pancreas

Abstract: The trophic effect of truncal vagotomy was studied in rats. Three months after vagotomy and pyloroplasty pancreatic weight was significantly increased by 40% (p < 0.001). Gastric stasis and consecutive distension of the stomach was observed in the majority of vagotomized animals despite pyloroplasty; the trophic effect of vagotomy on the pancreas was most pronounced in animals with severe stomach distension. Basal gastrin levels were increased after truncal vagotomy but did not correlate to gastric stasis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Vagotomy has previously been shown to increase the pancreatic weight [32][33][34], whereas this has not been found by others [3,22], Vagotomy did not influence the plasma concentration of CCK in the present study, but the results suggest a trophic influence of vagotomy on the pancreas. This seems to depend on other factors than a decreased body weight or hypergastrinemia.…”
Section: Discussioncontrasting
confidence: 92%
“…Vagotomy has previously been shown to increase the pancreatic weight [32][33][34], whereas this has not been found by others [3,22], Vagotomy did not influence the plasma concentration of CCK in the present study, but the results suggest a trophic influence of vagotomy on the pancreas. This seems to depend on other factors than a decreased body weight or hypergastrinemia.…”
Section: Discussioncontrasting
confidence: 92%
“…Truncal vagotomy has been suggested to exert a trophic effect on the exocrine pancreas [16], while studies by Büchler et al [4] indicated that pancreatic growth after truncal vagotomy depended rather on hyperplasia than on hypertrophy. Other authors have failed to show any effect on total or relative pancreatic weight or DNA content after truncal vagotomy in the rat [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, in case of such pancreatic insufficiency a certain degree of exocrine aci nar dystrophy might generally be expected [ 1 ]. On the other hand, truncal vagotomy has been shown to induce a direct trophic effect on the pancreas, resulting in a significant weight gain of all parts of the pancreas [39], This hypertrophy of the pancreas is probably related to the important hypergastrinemia that follows most forms of vagotomy, but may also be connected to the important gas tric stasis that was observed after truncal vagotomy and pyloroplasty [18]. Whereas in the study of Koop et al [ 18] this pancreatic hypertrophy did not result in a rise of amy lase or lipase production from the exocrine acini, it certainly did not lead to a dimin ished pancreatic enzyme secretion.…”
Section: Discussionmentioning
confidence: 99%